'Come. Open Your Eyes. Listen … I Hear Another Voice': The Voice, Time and Memory in Luciano Berio's Altra Voce (1999). Issue 3 (3rd May 2020) - Brady, Clare
Abstract : The human voice played a significant part in the compositions of Luciano Berio throughout his career, a preoccupation to which he returned again and again in order to examine, interrogate and celebrate its complex interactions with language, text, music, time and memory. This article examines the human voice in situ, in the context of a live performance of one of Berio's late chamber pieces, Altra Voce (1999), comprising alto flute, mezzo soprano and live electronic processes. I argue that the human voice in musical performance inhabits a number of simultaneous, often paradoxical positions, giving rise to an inherent mutivalency of form: in Altra Voce, we find these multiple facets presented in a crystalline, multi-voiced musical construction. This analysis of the work is drawn from both a reflection on the printed score and from the author's own experience of its realisation as a listening performer, the better to 'hear' the multi-layered, polyphonic texture to its fullest extent. To examine and articulate the complexities of the voice's interaction with time, memory and human interiority, this article draws on a number of tools, including musical and hermeneutic analysis, as well as a theoretical framework suggested by Jacques Derrida's discussion of presence and time, found in his 1967 work Speech and Phenomena . I argue that what Berio's Altra Voce demonstrates, and what resonates with Derrida's argumentation, is the paradoxical relationship between the seemingly fixed moment of 'live' vociferation and the passage of time. In conclusion, this article suggests that Altra Voce presents a dialectical co-existence of these seemingly irreconcilable aspects, demonstrating the inherent and paradoxical multivalency of the human voice in every musical performance.